Karyotype Evolution of Chagas Disease Vectors (Hemiptera, Triatominae) - Chaboli Alevi, Kaio Cesar [UNESP]; Oliveira, Jader de [UNESP]; Rosa, Joao Aristeu da [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP] (Amer Soc Trop Med & Hygiene, 2018)
The Triatominae subfamily is composed of 153 hematophagous species that are potential vectors of Trypanosoma cruzi, the etiological agent of Chagas disease. Karyotypic studies in triatomines were initiated in 1909. There are 92 karyotypes described, all grouped into the tribes Rhodniini and Triatomini. Recently, a phylogenetic study of the triatomines that combines molecular data with geological changes was performed. We now discuss how the karyotype evolved with the diversification of the triatomines.